The philosophy, aim and concept of education in Islam, its challenges in the curriculum design of integrated Islamic education in Malaysia - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (2018)
The first clause of education in Islam is to inculcate in the mind of learners the concept of God through the contemplation of Allah’s attributes by instilling taqwa and iman and ultimately to make man as an obedient and grateful servant to Allah who would lead a successful life in this world and Hereafter. Contrary to their remarkable history in the past, Muslims in the 21st century struggle to revive a genuine Islamic philosophy of education relevant to the modern world while they are grappling with the challenges of modernity in myriad ways. As a result, many are found to be indifferent with the knowledge they gained especially when it contradicts with their personal inclination and desires. Corruption, nepotism and kleptocracy are among the common crises faced by the Muslim countries throughout the world. Many concerned Muslim scholars have argued that the root of these crises is the disintegration of knowledge and education from Islamic worldview. Employing qualitative method of research, this paper strives to identify the philosophy of education in Islam, its aim, concept and challenges in the current integrated educational system, which is currently implemented in Malaysian schools and colleges. This paper contends to argue that the system, albeit its Islamic objectives, remains predominantly secular in view of its philosophy and methodology